The Gambia : Enhanced Heavily Indebted Poor Countries Initiative; Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2008)
An assessment is provided of The Gambia's performance in meeting the requirements for reaching the completion point under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative is provided. Next, the paper reviews the status of creditor participation and presents an updated debt sustainability analysis (DSA). The paper contains a summary of the main conclusions, and lists a number of issues for discussion by the Boards of IDA and the IMF. The poverty database and monitoring capacity has been improved. Macroeconomic performance under the third poverty reduction growth facility (PRGF)-supported program has been strong.